2021
DOI: 10.1097/pr9.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

Doctor shopping among chronic noncancer pain patients treated with opioids in the province of Quebec (Canada): incidence, risk factors, and association with the occurrence of opioid overdoses

Abstract: Introduction: Prescription opioids continue to be involved in the opioid crisis, and a better understanding of factors associated with problematic opioid use is needed. Objectives: The aim of this study was to assess the incidence of opioid doctor shopping, a proxy for problematic opioid use, to identify associated risk factors, and to assess its association with the occurrence of opioid overdoses. Methods: This was a retrospective cohort study of people living with chronic noncancer pain (CNCP) and treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Finally, the significant contribution of the number of prescribers concords with prior research 13 . The significance of multiple providers and high healthcare use has been attributed to doctor shopping, where patients visit multiple physicians to obtain multiple opioid prescriptions 51–53 . However, the 1‐year prevalence of opioid doctor shopping in Quebec in chronic noncancer pain is low (7%), represented mostly by young males with anxiety 52 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Finally, the significant contribution of the number of prescribers concords with prior research 13 . The significance of multiple providers and high healthcare use has been attributed to doctor shopping, where patients visit multiple physicians to obtain multiple opioid prescriptions 51–53 . However, the 1‐year prevalence of opioid doctor shopping in Quebec in chronic noncancer pain is low (7%), represented mostly by young males with anxiety 52 .…”
Section: Discussionmentioning
confidence: 89%
“…13 The significance of multiple providers and high healthcare use has been attributed to doctor shopping, where patients visit multiple physicians to obtain multiple opioid prescriptions. [51][52][53] However, the 1-year prevalence of opioid doctor shopping in Quebec in chronic noncancer pain is low (7%), represented mostly by young males with anxiety. 52 These findings are still of strong importance given that in Quebec, 30% of individuals are not attached to a GP, and may consult walk-in clinics or emergency departments when health services are required, which may in part be contributing to the problem of opioid use and PIOU, 54 although this is more likely to affect middle-aged individuals.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Schneberk et al 10 defined COPs as those who received greater than 6 or more prescriptions from at least 6 different prescribers within 6 months. Kaboré et al 26 defined a COP as an individual with at least 1 day of overlapping prescriptions written by at least 2 different prescribers and filled in at least 3 different pharmacies. Our selection of the time window to identify COP considered the average number of days of opioid analgesic supply to treat acute pain.…”
Section: Methodsmentioning
confidence: 99%
“…When patients with a prior drug abuse and addiction history were excluded, approximately 0.19% developed abuse and addiction to prescribed opioids [83]. A 2019 Cochran review reported signs of addiction in 0.27% of patient on long-term opioid therapy for NCRP [78], A 2021 Canadian study [84] identified doctor shopping in only 7.8%. When addiction was present it did not appear to correlated with opioid prescribing patterns.…”
Section: Abuse/addictionmentioning
confidence: 99%